2017
DOI: 10.1104/pp.17.00825
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Optimization of a Large Gene Coexpression Network in Maize Using RNA-Seq Data

Abstract: ORCID IDs: 0000-0002-6182-800X (J.H.); 0000-0001-6612-3570 (S.V.); 0000-0002-9564-8146 (K.M.M.).With the emergence of massively parallel sequencing, genomewide expression data production has reached an unprecedented level. This abundance of data has greatly facilitated maize research, but may not be amenable to traditional analysis techniques that were optimized for other data types. Using publicly available data, a gene coexpression network (GCN) can be constructed and used for gene function prediction, candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 116 publications
1
47
0
Order By: Relevance
“…Increasing sample size was reported to generally have a positive effect on network performance (Ballouz et al, 2015;Huang et al, 2017) -consistent with our comparison of tissue-specific or genotype-specific (i.e., developmental atlas) networks of different sizes. Interestingly, this is not always the case when comparing networks constructed from samples spanning multiple tissues of the same genotype panel (i.e., "metanetworks") to the various tissue-specific networks (i.e., using only samples from the same tissue for the genotype panel).…”
Section: The Value Of Multiple Networksupporting
confidence: 88%
“…Increasing sample size was reported to generally have a positive effect on network performance (Ballouz et al, 2015;Huang et al, 2017) -consistent with our comparison of tissue-specific or genotype-specific (i.e., developmental atlas) networks of different sizes. Interestingly, this is not always the case when comparing networks constructed from samples spanning multiple tissues of the same genotype panel (i.e., "metanetworks") to the various tissue-specific networks (i.e., using only samples from the same tissue for the genotype panel).…”
Section: The Value Of Multiple Networksupporting
confidence: 88%
“…This result can be attributed to either biased GOBP annotations toward evolutionarily conserved processes rather than plant-specific ones in maize, or biased availability of high-quality functional genomics data toward animals and yeast. Subsequently, we compared MaizeNet with other maize gene networks based on the protein-protein interaction database for maize (PPIM) (Zhu et al, 2016), gene coexpression (GCN) (Huang et al, 2017) and integration of multiple types of interactions (STRING10.5) (Szklarczyk et al, 2017) (Table 2). This comparison revealed that the range of AUROC (FPR < 0.01) for MaizeNet was significantly higher than that of the other maize gene networks (P < 0.001, Wilcoxon signed rank test) ( Figure 2b), thereby indicating that MaizeNet is among the most predictive gene networks for biological processes in maize.…”
Section: Assessment Of the Predictive Power Of Maizenetmentioning
confidence: 99%
“…This is true for transcriptomics data, which can be imported and visualized on a network by following the same steps we showed for proteomics data, as well as for phenotypic screens and mutation data. For example, the stringApp has already been used in the literature for network analysis of microarray data on the mammalian circadian pacemaker 21 and for comparing a coexpression network obtained from maize RNA-seq data to a network from STRING 22 .…”
Section: Discussionmentioning
confidence: 99%